2013
DOI: 10.1002/bjs.8959
|View full text |Cite
|
Sign up to set email alerts
|

Integration of patient-reported outcome measures with key clinical outcomes after immediate latissimus dorsi breast reconstruction and adjuvant treatment

Abstract: Background: Clinical evidence on patient-reported outcome measures (PROMS) in breast reconstruction is lacking. The aim of this study was to evaluate PROMs in implant-assisted latissimus dorsi (LDI) or tissue-only autologous latissimus dorsi (ALD) flap reconstruction in relation to complications and adjuvant treatments. Early complications up to 3 months after surgery were reported in 66 and 51·0 per cent of patients in the LDI and ALD groups respectively (P = 0·062) and long-term complications (4-12 months) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 28 publications
5
42
1
2
Order By: Relevance
“…We were unable to pool data for predictors from studies that used different continuous outcome measures to assess persistent pain in linear regression models. 36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationssupporting
confidence: 78%
See 1 more Smart Citation
“…We were unable to pool data for predictors from studies that used different continuous outcome measures to assess persistent pain in linear regression models. 36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationssupporting
confidence: 78%
“…¶Quality was not rated down on the basis of imprecision, even though the 95% CI for the pooled effect overlapped a risk difference of 0 (no effect), because clinical actions based on the estimate of the lower or upper boundary would not change, according to the predefined threshold of ≥ 20% for nonmodifiable factors. the 7 studies 37,39,42,50,53,55,56 that reported 1 or more of the 9 predictors that we subjected to metaanalysis but whose data could not be pooled were consistent with our pooled analyses (Appendix 9, available at www.cmaj.ca/lookup/ suppl/doi:10.1503/cmaj.151276/-/DC1).…”
Section: Predictors Of Persistent Painsupporting
confidence: 64%
“…Lower complication rates have been observed with immediate expander/implant reconstructions (21.7%), versus latissimus dorsi (LD) flap reconstructions (67.9%) or TRAM flap reconstructions (26.9%), while reoperation rates were lower for TRAM flap reconstruction (5.8% versus 11.3% for expander/implant and 10.7% for LD flap) (55). While implant-assisted LD reconstruction and tissue-only autologous LD flap reconstruction have demonstrated equivalent short-term (zero to three months) and long-term (four to 12 months) complication rates (66% versus 51%, respectively [P=0.062] and 48% versus 45%, respectively [P=0.845]), role functioning and pain were significantly worse in the tissue-only group (P=0.002 for both) (56). Recommendations: Several types of breast reconstruction are available: these include implant-based reconstructions, combination reconstructions (ie, LD flap with implant), and autologous flap reconstructions using deep inferior epigastric perforator (DIEP), TRAM, or superficial inferior epigastric artery flaps.…”
Section: What Types Of Breast Reconstruction Are Available?mentioning
confidence: 98%
“…Historically, QoL issues may have had a stronger focus in advanced cancer care and palliative medicine (Cella, 1995; Bottomley et al, 2005; Groenvold et al, 2006; Byrne et al, 2007; Abernethy et al, 2010; Cella et al, 2011; Amdal et al, 2013), but is now gaining importance in several fields for which curative surgery may be the central point in the care bundle for patients with cancer (Tan et al, 2012; Williamson et al, 2012a,b; Macefield et al, 2013; Pusic et al, 2013; Winters et al, 2013). Patient satisfaction (as a PROM) with hospital care is indeed independent of morbidity, treatment type, and QOL outcomes (Avery et al, 2006) – emphasizing the fact that PROMs may capture feedback information to providers not easily obtained through other metrics.…”
Section: Proms In Surgical Cancer Care and Researchmentioning
confidence: 99%